Organizational Justice As A Determinant Of Organizational Commitment And Intention To Leave - Hassan, Arif (Asian Academy of Management (AAM), 2002)
This paper presents the findings of a study, which investigated how perception of equity and justice played an important role in employees' commitment to the organization and intent to leave. The sample consisted of 181 middle and lower level managers from the banking and finance, production and manufacturing, and service sectors. The results hypothesized that both internal and external equity perceptions are positively related to commitment and negatively related to intent to leave. Among all the facets, equity promotion appeared to be the most significant predictor. Both distributive and procedural justice factors made significant contributions to employees' organizational commitment and intent to leave.